A practical approach for the derivation of algebraically stable two-step Runge-Kutta methods - Conte, Dajana; D'Ambrosio, Raffaele; Jackiewicz, Zdzislaw; Paternoster, Beatrice (Mathematical Modelling and Analysis, 2012)
We describe an algorithm, based on a new strategy recently proposed by Hewitt and Hill in the context of general linear methods, for the construction of algebraically stable two-step Runge-Kutta methods. Using this algorithm we obtained a complete characterization of algebraically stable methods with one and two stages.